EFEKTIVITAS PEMANTAUAN PERTUMBUHAN BALITA BERBASIS TEKNOLOGI INFORMASI TERHADAP KINERJA SISTEM INFORMASI GIZI DI DINAS KESEHATAN KABUPATEN SUKOHARJO - Widodo, Agus; ., Mutalazimah; Handaga, Bana (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
ABSTRACT Background. The research was conducted to develop the information system model on nutrition status of child monitoring based on information technologi support the plan of increasing the nutrition improvement at the District Health Office, Sukoharjo Regency. This descriptive research was carried out by implementing interview to subjects who were involved in the activity of the monitoring. Observation was also performed to two objects, namely the structure and the procedure of information. Method. The collected data were analysed descriptively by applying result of structure and the procedure analysis. The system development was designed by using the approach of FAST (Framework for the Application of System Techniques) and by using the tools of Data Flow Diagram and Entity Relationship Diagram. Results. The observation to the problem, its scope and property as well as the interview with the subjects indicate that the research subjects at all levels from top managers to persons in the transactional level as well as those who are at cross section department support the development of monitoring system to the improvement of nutrition status program, and this system is reliable to maping perform of nutrition status of child based on the category as severe malnutrition, under nutrition, normal and overweigt. In the future nutrition information based on information technologi have the benefits of the new system in supporting the monitoring activity toward the nutrition improvement program and it also supports the plan. Keywords: IT, monitoring, child nutrition status References: 15 (1997-2005)